Can mastication in children with cerebral palsy be analyzed by clinical observation, dynamic ultrasound and 3D kinematics?. (February 2017) - Remijn, L.; Groen, B.E.; Speyer, R.; van Limbeek, J.; Vermaire, J.A.; van den Engel-Hoek, L.; Nijhuis-van der Sanden, M.W.G.
Abstract: The aim of this study was to explore the feasibility of the Mastication Observation and Evaluation (MOE) instrument, dynamic ultrasound and 3D kinematic measurements to describe mastication in children with spastic cerebral palsy and typically developing children. Masticatory movements during five trials of eating a biscuit were assessed in 8 children with cerebral palsy, spastic type (mean age 9.08 years) and 14 typically developing children (mean age 9.01 years). Differences between trials were tested ( t -test) and the mastication of individual children with cerebral palsy was analyzed. MOE scores ranged from 17 to 31 (median 24) for the children with cerebral palsy and from 28 to 32 (median 31) for the typically developing children. There was an increased chewing cycle duration, a smaller left-right and up-down tongue displacement and larger anterior mandible movements for the trials (n = 40) of cerebral palsy children (p < 0.000 for all comparisons) compared to the trials of typically developing children (n = 70). The MOE captures differences in mastication between individual children with cerebral palsy. The MOE items 'jaw movement' and 'fluency and coordination' showed the most similarity with the objective measurements. Objective measurements of dynamic ultrasound and 3D kinematics complemented data from the MOE instrument.